Investigation of CD73 expression in Iraqi patient women with breast tumors - Raghdah Naser Mohsin; Ban Jasim Mohamad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Biomarkers that aid in the diagnosis, prognosis, and prediction of breast cancer are critical for early detection and effective disease management throughout treatment. Although preclinical studies suggest that 5-ectonucleotidase (CD73) could be a diagnostic marker in several types of cancer, it can be an appealing treatment strategy in some molecular subgroups of breast cancer. The aim of this study is to investigate the expression of CD73 in breast tumors (malignant and benign) in Iraqi patients using immunohistochemistry (IHC), as well as its correlation with clinicopathological characteristics. A total of eighty-nine samples of paraffin embedded tissue blocks of different breast tissue tumors (71 females and 18 were males) with their data in addition to eleven cases of healthy breast biopsies as a control were collected from public and private hospitals and health institutions in Baghdad. The findings of this task demonstrated substantial variations in the expression of CD73 between breast malignant, benign tumors and control groups (P < 0.001). CD73 expression was highest in 75.56% of malignant cases, while only 31.82% of benign cases showed positive expression of CD73. Furthermore, significant associations were found between CD73 with gender and histological types in benign cases and with (ER, PR, HER-2) negative and triple negative molecular subtypes in malignant cases. There were no significant variations in CD73 expression with other clinicopathological features. This allowed us to suggest that inhibiting CD73 could be an appealing treatment strategy in the TNBC subgroup.